Tricorythopsis nupem: a new species for the Atlantic forest from southeast Brazil (Ephemeroptera: Leptohyphidae) - Araújo, Vinícius Albano; Dias, Lucimar Gomes (Zootaxa, 2020)
Tricorythopsis Traver, 1958 is a neotropical genus of the Leptohyphidae (Ephemeroptera, Ephemerelloidea), with 19 species described (Molineri 2001; Dias & Salles 2005; Dias et al. 2008, 2009; Lima et al. 2011; Belmont et al. 2011, 2012, 2015; Domínguez et al. 2019). The genus comprises species of approximately two or three millimeters, and can be considered one of the smallest members of the order (Molineri 1999, 2001; Dias & Salles 2005; Dias et al. 2006, 2008, 2009; Belmont et al. 2011, 2015).